''Casuals' culture. Bricolage and consumerism in football supporters' culture. Case study – Dinamo Bucharest Ultras'. (10th November 2017) - Guțu, Dinu
Abstract : 'Casuals' culture can be perceived as a postmodern phenomenon, which modifies and changes the football supporter culture in a fully blown consumerist era, where symbol movement is faster every day and implies minimal costs. Throughout this article, I attempted to prove the existence of a certain type of 'bricolage', created by recycling a set of brands, symbolically redefined by ultras groups. At the same time, the internalization of the 'casuals' movement by Romanian fanatical supporters also denotes the emergence of strong elements of hyper-consumerist culture, of differentiation and status, both at the level of individuals in the groups, as well as at the level of rival supporters groups. 'Casuals' style naturally matches the entrance of football and of the culture of supporting a team into postmodernity.